2019
DOI: 10.1016/j.proci.2018.06.209
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble-LES analysis of perturbation response of turbulent partially-premixed flames

Abstract: The response to small perturbations of the Sandia CH 4 /air flame series is studied using a dynamical systems formulation. Here, the Sandia D and E turbulent partially-premixed flames are computed using large eddy simulation (LES) with a flamelet/progress variable approach. Using 300 simultaneous LES computations of each flame, the partial Lyapunov spectrum of the flow is obtained, which provides a set of Lyapunov exponents (LEs) and Lyapunov vectors (LVs). Special numerical procedures to handle such large dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The interplay between these contrasting features leads to significant spatio-temporal complexity [4,5,16,17], from intermittent disorder, through to chaos and turbulence: "turbulence" in the Kuramoto-Sivashinsky PDE is typically described as weak, incipient or localized, rather than fully turbulent; however, this regime provides mathematical insights into the transition from dynamical chaos to true turbulence [17,24]. Lyapunov exponents characterize this chaos and turbulence [8,27,34], and are increasingly used to analyse such spatio-temporal complexity in various applications such as turbulent Poiseuille flow [19], turbulence in flames [14] and Rayleigh-Bérnard fluid convection [2,36].…”
Section: Introductionmentioning
confidence: 99%
“…The interplay between these contrasting features leads to significant spatio-temporal complexity [4,5,16,17], from intermittent disorder, through to chaos and turbulence: "turbulence" in the Kuramoto-Sivashinsky PDE is typically described as weak, incipient or localized, rather than fully turbulent; however, this regime provides mathematical insights into the transition from dynamical chaos to true turbulence [17,24]. Lyapunov exponents characterize this chaos and turbulence [8,27,34], and are increasingly used to analyse such spatio-temporal complexity in various applications such as turbulent Poiseuille flow [19], turbulence in flames [14] and Rayleigh-Bérnard fluid convection [2,36].…”
Section: Introductionmentioning
confidence: 99%
“…Chaotic systems naturally appear in many branches of science and engineering, from turbulent flows [e.g., 1, 2, 3], through vibrations [4], electronics and telecommunications [5], quantum mechanics [6], reacting flows [7,8], to epidemic modelling [9], to name only a few. The time-accurate computation of chaotic systems is hindered by the "butterfly effect" [10]: an error in the system's knowledge-e.g, initial conditions and parameters-grows exponentially until nonlinear saturation.…”
Section: Introductionmentioning
confidence: 99%
“…In statistically stationary flows, it is hypothesized that the trajectory followed by the flow in this high-dimensional state space is confined to a low-dimensional subspace. There have been many attempts to characterize the size of this subspace [35][36][37]39,40 . While theoretical scaling suggests that the manifold dimension will increase as Re n , where n > 2, in statistically stationary turbulence 38 , more recent numerical studies have concluded that the manifold may be lower dimensional.…”
Section: Introductionmentioning
confidence: 99%
“…While theoretical scaling suggests that the manifold dimension will increase as Re n , where n > 2, in statistically stationary turbulence 38 , more recent numerical studies have concluded that the manifold may be lower dimensional. For instance, application to the Sandia flame series 40 showed that the dimension is much smaller than the degrees of freedom generated by discretization.…”
Section: Introductionmentioning
confidence: 99%